Faktor Risiko Computer Vision Syndrome (CVS) pada Mahasiswa pada Masa Pandemi Covid-19 - Alifia Merza Safaryna; Dian Prasasti Kurniawati; Fariani Syahrul; Reni Prastyani (Media Gizi Kesmas, 2023)
Background: Sophisticated technology provides many conveniences for humans, as well as education that cannot be separated from it, especially during this COVID-19 pandemic in which the learning methods are carried out online. This is what causes the intensity of using a computer or laptop to increase so that it can trigger the occurrence of visual impairment, namely Computer Vision Syndrome (CVS). There is no definite data regarding CVS and CVS research on university students, especially in Surabaya, is still very small. Objectives: This study aims to analyze the risk factors for CVS among college students during the COVID-19 pandemic. Methods: This research was analytic observational research with a cross-sectional research design. This research was conducted from December 2020 to June 2021. The sampling method used was a systematic random sampling addressed to 249 Public Health undergraduate students from the second, fourth, and sixth semesters. The instrument used was CVS-Q with additional questions related to respondent identity, medical history, and computer-usage behavior. Furthermore, the data were analyzed by calculating the Odds Ratio (OR) with a 95% confidence interval (CI). Results: Gender (OR = 2.54) and a history of eye disorders (OR = 4.01) were risk factors for Computer Vision Syndrome (CVS) in S1 Public Health Science students. Conclusions: This research shows that the risk factors for CVS are gender and a history of eye disorders. The students who use computers with high intensity should take CVS precautions, such as applying the 20-20-20 rule, using anti-radiation glasses, adjusting the brightness of the computer screen, adding an anti-glare on the computer screen, avoiding working in a dark room, and performing an ergonomic body position when using a computer.